LINGKUNGAN KERJA, ETOS KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Arum, Rosita Sekar; Rahmawati, Esti Dwi; Suyatno, Agus (PT Naureen Digital Education, 2023)
The achievement of a company's goals is the company's success in managing its human resources. This is a form of human capital or human capital whose value is entirely in the form of talent, knowledge, performance, experience and motivation that the workforce has for the company. Therefore, this research aims to determine how influential the work environment variables, work ethos and work discipline on employee performance at the Baru Toserba Wonogiri. This research uses a quantitative method with multiple linear regression analysis. The sample used was 80 respondents from a total population of 240 employees at Baru Toserba Wonogiri. Collecting data in this research using a questionnaire to employees at the Baru Toserba Wonogiri. From the results of the research it was obtained that partially, the work environment (X1) has a positive and significant effect on employee performance (Y), work ethos has a positive and significant effect on employee performance (Y), and work discipline has a positive and significant effect on employee performance (Y). The results simultaneously (together) obtained that the work environment (X1), work ethos (X2), and work discipline (X3) have a positive and significant effect on employee performance (Y) at Baru Toserba Wonogiri